Economic cycle and deceleration of female labor force participation in Latin America - Joaquín Serrano; Leonardo Gasparini; Mariana Marchionni; Pablo Gluzmann (Journal for Labour Market Research, 2019)
We study the behavior of female labor force participation (LFP) over the business cycle by estimating fixed effects models at the country and population-group level, using data from harmonized national household surveys of 18 Latin American countries in the period 1987-2014. We find that female LFP follows a countercyclical pattern-especially in the case of married, with children and vulnerable women-which suggests the existence of an inverse added-worker effect. We argue that this factor may have contributed to the deceleration in female labor supply in Latin America that took place in the 2000s, a decade of unusual high economic growth.
Keywords: J16; J22; N3; 330; Economic cycle; Female labor force participation; Latin America